Profile of Junior High School Students' Problem-Solving Ability on The Topic of Human Relationship to Ecosystems Through The Role-playing Method - Alvi Rohmah; Indra Fardhani; Dian Nugraheni; Habiddin Habiddin (PT Ahan Group Publisher, 2025)
This research aims to elucidate the problem-solving capabilities of junior high school students about human relationships with ecosystems, particularly river ecosystems, utilising the role-playing method within a debate framework among represented professional groups. This study involved 25 seventh-grade students from an MTs Negeri in Malang Regency. Students were grouped to simulate various occupations, including physicians, government representatives, scientists, and environmental advocates. Data was gathered using LKPD responses, observation forms, and interview protocols. The data analysis indicates that the environmental volunteer profession group scored the highest on the LKPD, scoring 94. Additionally, as assessed by observation, the average percentage derived from the student problem-solving skill profile was 85%, categorised as very good. The interview results indicated that students responded positively to the learning activities.